Let $\displaystyle f(x) = x^2 - 2x$, $\displaystyle x\in \mathbb{R}$ and $\displaystyle g(x) = f(f(x) - 1) + f(5 - f(x))$. Show that $\displaystyle g(x)\geq 0\ \forall\ x\in \mathbb{R}$.

Printable View

- May 23rd 2009, 10:20 PMfardeen_genProve that g(x) greater than/equal to 0?
Let $\displaystyle f(x) = x^2 - 2x$, $\displaystyle x\in \mathbb{R}$ and $\displaystyle g(x) = f(f(x) - 1) + f(5 - f(x))$. Show that $\displaystyle g(x)\geq 0\ \forall\ x\in \mathbb{R}$.

- May 24th 2009, 02:23 AMIsomorphism